Perfomance Ayam Broiler Dengan Manajemen Perkandangan Sistem closed house dan open house - sm, ilpan (Program Studi Peternakan Universitas Muhammadiyah Sidenreng Rappang, 2024)
The aim of this research is to determine the efficiency of using the closed house cage and open house cage management systems owned by PT partners. Poultry Technology Integration. This study used an observational approach by comparing feed consumption, body weight gain, feed conversion ratio, final body weight, and mortality of broiler chickens reared in two different cages that were harvested in 1 rearing period. Data on feed consumption, body weight gain, feed conversion ratio and mortality were analyzed statistically using the t test, while data on final body weight were analyzed descriptively. Based on research findings, the average feed consumption in the closed house cage system is 3562.20 g/head and the feed consumption in the open house cage system is 3233.72 g/head. In the close house cage system, the average feed conversion ratio is 1.672 while in the open house cage system it is 1.517. Close house and open house cage systems had no significant difference (P > 0.05) on feed consumption. body weight gain, feed conversion ratio and mortality. The close house cage system produced a final body weight of 2,437 g/head while in the open house cage it was 1,991 g/head and the total mortality percentage of the close house cage system was 7.08% of the initial population of 5000 birds, while the open house cage system reached 10.32% of the 5000 initial population.